Analysis of Antenatal Care (ANC) Visits and Prenatal Classes for High-Risk Pregnancy : Compliance and Involvement of Couples - Wahyuningsih, Endang; Wahyuningsih, Astri; Ambarsari, Lusiana (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background: High-risk pregnancies present a significant threat to the health of both the mother and the fetus. Antenatal care (ANC) visits and prenatal classes play an essential role in monitoring and maintaining maternal and fetal health. Purpose: Analyzing the Level of Compliance of ANC Visits, Assessing the Involvement of Couples Method: This is a quantitative, descriptive study involving 14 high-risk pregnant women as the research sample, Small Sample using total sampling. The research instrument was a questionnaire. Data analysis was performed to obtain the distribution of frequency and percentage of physical activity and nutrition among high-risk pregnant women. Result: All respondents reported that most pregnant women had their first ANC examination in the first trimester and attended regular check-ups with obstetricians and midwives at private practices, health centers, hospitals, and clinics. The husbands of pregnant women also played an active role in the pregnancy process, providing fetal stimulation and accompanying their partners during check-ups. However, most participants did not attend prenatal classes, with 10 women (71.40%) opting out. Among those who participated in prenatal classes, 10 women (71.40%) attended fewer than four classes. Additionally, the majority of husbands did not participate in prenatal classes. Conclusion: Healthcare providers are encouraged to increase the involvement of husbands both during ANC visits and prenatal classes to enhance support for pregnant women. Prenatal classes should be designed to be as engaging as possible to increase the interest and participation of both pregnant women and their partners.